Ethical challenges regarding library integration with artificial intelligence - Nathania, Nisrina; Margono, Hendro; Mohamad Rosman, Mohamad Rahimi; Abdul Hamid, Haslinda; Md Radzi, Salliza (Faculty of Information Management, 2025)
The deployment of Artificial Intelligence (AI) in libraries offers both prospects and considerable ethical dilemmas. This research investigates the ethical ramifications of AI integration in library services, focusing on issues such as data privacy, algorithmic bias, transparency, job displacement, and the possible erosion of human contact. The study seeks to identify and classify significant ethical dilemmas while offering pragmatic advice for library stakeholders. This research employs a thorough literature review technique to assess current scientific papers and reputable sources over the last six years. The results identify six primary areas of ethical challenges: privacy and data security, algorithmic bias and discrimination, transparency and accountability, job displacement, loss of human connection, and the need for ethical frameworks and rules. The research indicates that while AI has substantial promise to enhance library services, meticulous assessment and proactive management of ethical concerns are essential. Future studies need to concentrate on such as empirical investigations, cross-cultural comparisons, and longitudinal evaluations of AI deployment in libraries.